Electrode comprising active material layer having bilayer structure and secondary battery comprising same
By adopting a double-layer electrode in the positive electrode of the lithium secondary battery, combining lithium iron phosphate and lithium nickel oxide active materials, and using needle-shaped and spherical conductive materials, the problems of insufficient thermal stability and adhesion in the prior art are solved, and high capacity and excellent thermal stability are achieved.
Patent Information
- Application Number
- CN202480004145.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-13
- Filing Date
- 2024-06-26
- Publication Date
- 2025-05-02
AI Technical Summary
Existing lithium secondary battery positive electrode active materials such as lithium nickel oxide materials have low thermal stability, while lithium iron phosphate materials have low adhesion and low capacity characteristics, making it difficult to meet the needs of high capacity and excellent thermal stability at the same time.
The electrode adopts a double-layer structure, the lower active material layer includes the first lithium iron phosphate active material and the lithium nickel oxide active material, and the upper active material layer uses the second lithium iron phosphate active material alone, and needle-shaped and spherical conductive materials are used respectively to improve conductivity.
While maintaining high capacity characteristics, the thermal stability of the electrode is significantly improved, and the overall performance of the electrode is improved by optimizing the distribution of conductive material.
Smart Images

Figure CN119923728A_ABST
Abstract
Description
Technical Field
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2023-0087746 filed on July 6, 2023 and Korean Patent Application No. 10-2024-0062275 filed on May 13, 2024, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a double-layer structured electrode and a secondary battery comprising the same, and more particularly, the electrode comprises different kinds of active materials. Background Art
[0003] Lithium secondary batteries are used as energy sources for various electronic devices, and as technology develops, there is an increasing demand for batteries capable of exhibiting larger capacity in the same space or design as compared with conventional batteries.
[0004] Lithium transition metal composite oxides are used as positive electrode active materials for such lithium secondary batteries. Generally, lithium nickel oxide-based active materials with high operating voltage and excellent capacity characteristics have been continuously studied. However, lithium nickel oxide-based active materials have the limitation of low thermal stability.
[0005] As an alternative method, research is being conducted on a technology that uses lithium iron phosphate as a positive electrode active material. However, lithium iron phosphate-based active materials have problems such as low adhesion to a current collector and low capacity characteristics.
[0006] Therefore, there is a need to develop a new technology that uses lithium iron phosphate oxide to improve thermal stability while retaining the characteristics of lithium nickel oxide active materials. Summary of the invention
[0007] Technical issues
[0008] Therefore, the present invention aims to provide an electrode for a secondary battery which maintains the capacity characteristics of a lithium nickel oxide active material and enhances thermal stability by using a lithium iron phosphate active material, and a secondary battery applying the electrode for a secondary battery.
[0009] Technical Solution
[0010] In order to solve the above problems, in one embodiment, the electrode for a secondary battery according to the present invention comprises:
[0011] Current collector;
[0012] a lower active material layer formed on one or both sides of the current collector, the lower active material layer comprising a first lithium iron phosphate active material (F1) and a lithium nickel oxide active material (N) as active materials, and comprising a needle-shaped conductive material as a conductive material; and
[0013] An upper active material layer is formed on the lower active material layer, the upper active material layer including the second lithium iron phosphate active material (F2) as an active material and including a spherical conductive material as a conductive material.
[0014] In one example, the ratio of the content of the sum of the first and second lithium iron phosphate active materials (F1+F2) to the content of the lithium nickel oxide active material (N) is in the weight ratio range of 55 to 70:30 to 45. In addition, the total loading amount of the lower and upper active material layers is 300 mg / 25 cm on average. 2 Up to 900 mg / 25cm 2 within the range.
[0015] In one embodiment, the upper active material layer uses a spherical conductive material alone as a conductive material, or uses 90% by weight or more of a spherical conductive material and the remainder of a needle-shaped conductive material as a conductive material. In this case, the lower active material layer may use a needle-shaped conductive material alone as a conductive material, or may use a mixture of spherical and needle-shaped conductive materials as a conductive material.
[0016] In another embodiment, the upper active material layer uses a spherical conductive material alone as the conductive material, or uses 90% by weight or more of a spherical conductive material and the remainder of a needle-shaped conductive material as the conductive material. In addition, the lower active material layer uses a mixture of a spherical conductive material and a needle-shaped conductive material in a weight ratio of 30 to 60:40 to 70 as the conductive material.
[0017] In another embodiment, the total loading of the lower and upper active material layers averages 400 mg / 25 cm 2 Up to 700 mg / 25cm 2 In addition, the secondary battery electrode according to the present invention satisfies a value calculated by the following condition 1 of 0.45 or less.
[0018] [Condition 1]
[0019] D 上 / D 下
[0020] Where D 上 represents the average loading of the upper active material layer (mg / 25cm 2 ),
[0021] Where D下 represents the average loading of the lower active material layer (mg / 25cm 2 ).
[0022] In one embodiment, the loading amount of the lower active material layer is 300 mg / 25 cm 2 Up to 450 mg / 25cm 2 within the range.
[0023] In another example, the ratio (F1:F2) of the content of the first lithium iron phosphate active material (F1) in the lower active material layer to the content of the second lithium iron phosphate active material (F2) in the upper active material layer is in the weight ratio range of 40 to 60:40 to 60.
[0024] In another example, in the lower active material layer, a ratio (F1:N) of a content of the first lithium iron phosphate active material (F1) to a content of the lithium nickel oxide active material (N) is in a weight ratio range of 35 to 48:52 to 65.
[0025] In one specific example, the total porosity of the lower and upper active material layers is in the range of 22% to 28% (volume / volume) on average. The porosity is calculated based on volume.
[0026] In one example, the first and second lithium iron phosphate active materials (F1, F2) are each independently represented by the following Chemical Formula 1.
[0027] [Chemical formula 1]
[0028] Li 1+a Fe 1-b M 1 b PO 4-c X c
[0029] Among them, M 1 Contains any one or two or more elements selected from Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn and Y,
[0030] wherein X comprises any one or more elements selected from F, S and N,
[0031] Wherein a, b and c are in the following ranges: -0.5≤a≤0.5, 0≤b≤0.9, 0≤c≤0.8 respectively.
[0032] For example, the first and second lithium iron phosphate active materials (F1, F2) each independently include a carbon coating.
[0033] In another example, the lithium nickel oxide active material (N) is represented by Chemical Formula 2 below.
[0034] [Chemical formula 2]
[0035] Li p Ni 1-q-r-s Co q Mn r M 2 s O 2
[0036] Among them, M 2 is any one or more elements selected from Al, Zr, Ti, Mg, Ta, Nb, Mo and Cr, and
[0037] 0.9≤p≤1.5, 0≤q≤1, 0≤r≤0.5, 0≤s≤0.1, 0≤q+r+s≤1.
[0038] For example, in Chemical Formula 2, 1-qrs is in the range of 0.2 to 0.95.
[0039] The present invention also provides a secondary battery, the secondary battery comprising the above-mentioned electrode for secondary battery. Specifically, the electrode can be used as a positive electrode. In one embodiment, the secondary battery is a structure comprising a positive electrode, a separator and a negative electrode. The separator can be arranged between the positive electrode and the negative electrode.
[0040] In one example, the secondary battery is a pouch type battery.
[0041] In another example, the secondary battery is a cylindrical or square type battery.
[0042] In another example, the secondary battery is a battery for an automobile or an energy storage system (ESS).
[0043] Beneficial Effects
[0044] The electrode for a secondary battery according to the present invention has an advantage of achieving excellent thermal stability while maintaining high capacity characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 and 2 1 is a cross-sectional view and an enlarged view of an electrode manufactured according to an embodiment of the present invention.
[0046] Figure 3 and 4 1 is a cross-sectional view and an enlarged view of an electrode manufactured according to a comparative example.
[0047] Figure 5FIG. 1 is a graph showing calculation results of shutdown speeds (TP speeds) of secondary batteries to which electrodes according to the embodiment and the comparative example are applied, respectively.
[0048] Figure 6 Graphs showing changes in capacity retention rates of secondary batteries to which electrodes according to the embodiment and the comparative example are applied, respectively, with respect to the number of cycles.
[0049] Figure 7 Graphs showing evaluation results of high-temperature storage characteristics of secondary batteries to which electrodes according to the embodiment and the comparative example are applied, respectively.
[0050] Figure 8 Graphs showing results of evaluating battery resistance according to SOC of secondary batteries to which electrodes according to the embodiment and the comparative example are applied, respectively.
[0051] Fig. 9 Graphs showing the evaluation results of adhesion of electrodes according to Examples and Comparative Examples.
[0052] Fig.10 It is a graph showing the evaluation results of the resistance of electrodes according to Examples and Comparative Examples. DETAILED DESCRIPTION
[0053] The present invention is susceptible to many variations and embodiments, so specific embodiments thereof will be described in detail below.
[0054] However, it should be understood that the present invention is not limited to the specific embodiments and includes all changes, equivalents or substitutes within the spirit and technical scope of the present invention.
[0055] The terms "include", "comprising" and "having" used in this document indicate the presence of features, numbers, steps, actions, components or members, or a combination thereof, described in the specification, and it should be understood that the presence or possibility of adding one or more other features, numbers, steps, actions, components, members, or a combination thereof are not precluded.
[0056] Furthermore, in the present invention, when a layer, film, region, plate, or the like is disposed "on" another part, this includes not only a case where a part is "directly" disposed "on" another part, but also a case where another part is interposed between the two. Conversely, when a layer, film, region, plate, or the like is disposed "under" another part, this includes not only a case where a part is "directly" disposed "under" another part, but also a case where another part is interposed between the two. Furthermore, in the present application, "on..." includes not only a case where it is disposed on an upper part, but also a case where it is disposed on a lower part.
[0057] Hereinafter, the present invention is described in more detail.
[0058] In one embodiment, the electrode for a lithium secondary battery according to the present invention comprises:
[0059] Current collector;
[0060] a lower active material layer formed on one or both sides of the current collector, the lower active material layer comprising a first lithium iron phosphate active material (F1) and a lithium nickel oxide active material (N) as active materials, and comprising a needle-shaped conductive material as a conductive material; and
[0061] An upper active material layer is formed on the lower active material layer, the upper active material layer including the second lithium iron phosphate active material (F2) as an active material and including a spherical conductive material as a conductive material.
[0062] The electrode for a secondary battery according to the present invention is a double-layer structure comprising a lower and upper active material layer. The lower active material layer contains a mixed active material comprising a first lithium iron phosphate active material (F1) and a lithium nickel oxide active material (N). The upper active material layer alone contains a second lithium iron phosphate active material (F2) as an active material. In addition, the lower active material layer contains a needle-shaped conductive material, and the upper active material layer contains a spherical conductive material.
[0063] Specifically, the ratio of the total content of the first and second lithium iron phosphate active materials (F1+F2) to the content of the lithium nickel oxide active material (N) is in the weight ratio range of 55 to 70:30 to 45. For example, the content ratio is in the weight ratio range of 55 to 65:35 to 45. In the electrode for a lithium secondary battery according to the present invention, the proportion of the lithium iron phosphate active material is controlled to be high based on the entire active material layer. In the present invention, excellent thermal stability can be achieved by controlling the content of the lithium iron phosphate active material (F1+F2) to be higher than the content of the lithium nickel oxide (N).
[0064] In addition, the total loading of the lower and upper active material layers averaged 300 mg / 25 cm 2 Up to 900 mg / 25cm 2 Specifically, the loading is 400 mg / 25 cm 2 Up to 700 mg / 25cm 2 or within 500 mg / 25cm 2 Up to 600 mg / 25cm 2 The secondary battery electrode according to the present invention may have a double-layer structure, thereby achieving a high load. For example, the electrode can be manufactured using a double-slit die (DLD). By using DLD to manufacture an electrode having a double-layer structure, a high load can be achieved, the interface properties between the upper and lower layers can be improved, and the process can be simplified.
[0065] The electrode for a secondary battery according to the present invention is characterized in that different conductive materials are applied to the upper and lower active material layers. The lower active material layer contains a needle-shaped conductive material, and a mixture of needle-shaped and spherical conductive materials can also be used. The lower active material layer contains a needle-shaped conductive material, which can improve the conductivity between the active materials and minimize the conductive material content. In this regard, the upper active material layer contains a spherical conductive material. The upper active material layer contains a lithium iron phosphate active material as an active material. More specifically, the upper active material layer contains a lithium iron phosphate active material alone as an active material. The average particle size of the lithium iron phosphate active material is in the range of 0.5 μm to 2 μm, more specifically in the range of 0.5 μm to 1.2 μm, or in the range of 0.6 μm to 0.8 μm. Since the particle size range of the lithium iron phosphate active material is small, the needle-shaped conductive material is not suitable. Specifically, even if a needle-shaped conductive material is used in the upper active material layer containing small-size lithium iron phosphate particles alone as an active material, the area in which the small-size lithium iron phosphate particles and the needle-shaped conductive material contact each other may be smaller than when a small-size spherical conductive material is mixed with the small-size lithium iron phosphate particles. Therefore, mixing the spherical conductive material with the lithium iron phosphate particles may be advantageous in improving conductivity.
[0066] In the present invention, by introducing a spherical conductive material into the upper active material layer using a lithium iron phosphate active material alone as the active material, the conductivity of the active material can be improved. These results are confirmed in the experimental examples that follow.
[0067] In a specific embodiment, the upper active material layer uses a spherical conductive material alone as a conductive material, or uses 90% by weight or more of a spherical conductive material and the remainder of a needle-shaped conductive material as a conductive material. In this case, the lower active material layer may use a needle-shaped conductive material alone as a conductive material, or may use a mixture of spherical and needle-shaped conductive materials.
[0068] In another specific embodiment, the upper active material layer uses a spherical conductive material alone as the conductive material, or uses 90% by weight or more of a spherical conductive material and the remainder of a needle-shaped conductive material as the conductive material. In addition, the lower active material layer uses a mixture of a spherical conductive material and a needle-shaped conductive material in a weight ratio of 30 to 60:40 to 70 as the conductive material. By including a specific amount of the spherical conductive material, the lower active material layer can improve durability against rolling.
[0069] In one embodiment, the total loading of the lower and upper active material layers is on average 400 mg / 25 cm 2 Up to 700mg / 25cm 2In addition, the secondary battery electrode according to the present invention satisfies a value calculated by the following condition 1 of 0.45 or less.
[0070] [Condition 1]
[0071] D 上 / D 下
[0072] Where D 上 represents the average loading of the upper active material layer (mg / 25cm 2 ),
[0073] Where D 下 represents the average loading of the lower active material layer (mg / 25cm 2 ).
[0074] Condition 1 refers to the loading ratio between the upper and lower active material layers. Specifically, the loading ratio according to condition 1 may be in the range of 0.1 to 0.45, in the range of 0.3 to 0.45, or in the range of 0.4 to 0.45. The present invention can maintain the capacity characteristics of the lithium nickel oxide active material by controlling the loading of the lower active material layer to be relatively high.
[0075] In one embodiment, the loading amount of the lower active material layer is 300 mg / 25 cm 2 Up to 450 mg / 25cm 2 For example, the loading amount of the lower active material layer is 300 mg / 25 cm 2 Up to 400 mg / 25cm 2 Within the range of 350 mg / 25cm 2 Up to 450mg / 25cm 2 within the range of 350 mg / 25cm 2 Up to 400 mg / 25cm 2 The present invention controls the loading amount of the lower active material layer to be relatively higher than the loading amount of the upper active material layer.
[0076] In another example, the ratio (F1: F2) of the content of the first lithium iron phosphate active material (F1) of the lower active material layer to the content of the second lithium iron phosphate active material (F2) of the upper active material layer is in the weight ratio range of 40 to 60: 40 to 60. For example, the ratio (F1: F2) is in the weight ratio range of 40 to 50: 50 to 60, in the weight ratio range of 45 to 60: 40 to 55, or in the weight ratio range of 45 to 55: 45 to 55. In the present invention, the contents of the lithium iron phosphate active materials respectively contained in the lower and upper active material layers are controlled at the same level. Therefore, the electrode for a secondary battery according to one embodiment of the present invention can achieve uniform thermal stability of the upper and lower active material layers.
[0077] In another example, in the lower active material layer, the ratio (F1:N) of the content of the first lithium iron phosphate active material (F1) to the content of the lithium nickel oxide active material (N) is in the weight ratio range of 35 to 48:52 to 65. For example, the ratio (F1:N) is in the weight ratio range of 35 to 45:55 to 65, in the weight ratio range of 40 to 48:52 to 60, or in the weight ratio range of 40 to 45:55 to 65. In the lower active material layer, the content of the lithium nickel oxide active material (N) can be controlled to be higher than the content of the first lithium iron phosphate active material (F1). In the present invention, the lower active material layer is a structure in which the first lithium iron phosphate active material is dispersed in the lithium nickel oxide matrix. Therefore, the lower active material layer has stronger characteristics of lithium nickel oxide. In an electrode for a secondary battery according to one embodiment of the present invention, the lower active material layer realizes the characteristics of a lithium nickel oxide active material, and the upper active material layer realizes the characteristics of a lithium iron phosphate active material. The lower active material layer helps to further improve the capacity of the electrode, and the upper active material layer helps to further improve the thermal stability of the electrode.
[0078] In the present invention, the total porosity of the lower and upper active material layers is in the range of 22% to 28% (volume / volume) on average. For example, the porosity is in the range of 24% to 26% (volume / volume) on average. The present invention provides low porosity by calendaring at high pressure. The present invention applies spherical conductive material to the upper active material layer, thereby minimizing the reduction in conductivity even when calendaring at high pressure.
[0079] In one embodiment, the first and second lithium iron phosphate active materials (F1, F2) are each independently represented by the following Chemical Formula 1.
[0080] [Chemical formula 1]
[0081] Li 1+a Fe 1-b M1 b PO 4-c X c
[0082] Among them, M 1 Contains any one or two or more elements selected from Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn and Y,
[0083] wherein X comprises any one or more elements selected from F, S and N,
[0084] Wherein a, b and c are in the following ranges: -0.5≤a≤0.5, 0≤b≤0.9, 0≤c≤0.8 respectively.
[0085] In Chemical Formula 1, for example, b is in the range of 0 to 0.7, 0.1 to 0.9, 0.3 to 0.9, 0.3 to 0.7, or 0.5 to 0.9. In one example, in Chemical Formula 1, b is in the range of 0.61 to 0.85, which can increase the operating voltage range of the electrode.
[0086] In a specific example, the active material according to Chemical Formula 1 is Li 1+a FePO 4 (-0.3≤a≤0.3) and Li 1+a Fe 1-b Mn b PO 4 (-0.3≤a≤0.3, 0.3≤b≤0.9) or more. For example, the active material according to Chemical Formula 1 is LiFePO 4 、LiFe 0.7 Mn 0.3 PO 4 、LiFe 0.5 Mn 0.5 PO 4 and LiFe 0.3 Mn 0.7 PO 4 One or more of the following.
[0087] In another example, the active material according to Chemical Formula 1 may be a carbon (C) coated structure. Through carbon coating, the conductivity of the active material according to Chemical Formula 1 can be improved.
[0088] In another example, the lithium nickel oxide active material (N) is represented by Chemical Formula 2 below.
[0089] [Chemical formula 2]
[0090] Li p Ni 1-q-r-s Coq Mn r M 2 s O 2
[0091] wherein M 2 is any one or more elements selected from Al, Zr, Ti, Mg, Ta, Nb, Mo, and Cr, and
[0092] 0.9 ≤ p ≤ 1.5, 0 ≤ q ≤ 1, 0 ≤ r ≤ 0.5, 0 ≤ s ≤ 0.1, 0 ≤ q + r + s ≤ 1.
[0093] Specifically, the active material according to Chemical Formula 2 can be expressed as Li p (Ni 1-q-r Co q Mn r )O 4 (0.5 < p < 1.3, 0 < q < 1, 0 < r < 1). For example, in Chemical Formula 2, q and r are each independently in the range of 0.05 to 0.9, 0.1 to 0.8, or 0.1 to 0.3. More specifically, in Chemical Formula 2, 1 - q - r - s is in the range of 0.2 to 0.95, or in the range of 0.5 to 0.7.
[0094] The secondary battery electrode according to an embodiment of the present invention is formed by simultaneously coating a lower and an upper active material layer on a current collector by applying a simultaneous coating technique using a double - layer slit die (DLD) device. Accordingly, the electrode has excellent electrode manufacturing efficiency and can achieve a high loading amount.
[0095] The secondary battery electrode as described above has a structure in which an active material layer is formed on a current collector. In the present invention, the active material layer includes a lower active material layer and an upper active material layer. With respect to 100 parts by weight of the active material layer, the content of the active material can be 85 parts by weight to 98 parts by weight, more specifically 90 parts by weight to 98 parts by weight, or 95 parts by weight to 98 parts by weight.
[0096] In addition, in addition to the active material, the active material layer may further include a conductive material, a binder, and / or a dispersant.
[0097] In this case, the conductive material is used to improve the performance of the positive electrode, such as conductivity. The needle - shaped conductive material may be carbon fiber, carbon nanofiber (CNT), or a pulverized product thereof. The spherical conductive material may be at least one selected from carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal - cracking carbon black. For example, the spherical conductive material may be carbon black, and the needle - shaped conductive material may include carbon nanofiber (CNT).
[0098] In addition, the content of the conductive material can be in the range of 0.1 to 5 parts by weight, 0.2 to 3 parts by weight, 0.3 to 1.5 parts by weight, or 0.5 to 1.2 parts by weight relative to 100 parts by weight of the active material layer. By applying carbon nanofibers (CNTs) as the conductive material, the content of the conductive material can be reduced while maintaining electrical conductivity.
[0099] In addition, the binder may include one or more resins selected from polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate and copolymers thereof. In one example, the binder may include polyvinylidene fluoride.
[0100] In addition, the binder may be included in an amount of 1 to 10 parts by weight, more specifically 2 to 8 parts by weight, or 2 to 5 parts by weight, relative to 100 parts by weight of the entire active material layer.
[0101] On the other hand, as a collector of a positive electrode for a lithium secondary battery according to an embodiment of the present invention, a collector having high conductivity and not causing chemical changes in the battery can be used. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. can be used, and in the case of aluminum or stainless steel, aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can also be used. In addition, the collector can form fine concave-convex on the surface to improve the adhesion of the positive electrode active material, and can be in various forms, such as a film, a sheet, a foil, a net, a porous body, a foam, a non-woven fabric, etc. In addition, considering the conductivity and total thickness of the positive electrode to be manufactured, the average thickness of the collector can be appropriately applied to 3 μm to 500 μm.
[0102] Secondary battery
[0103] In one embodiment, the present invention also provides a secondary battery, the secondary battery comprising the above-mentioned secondary battery electrode. Specifically, the present invention provides a secondary battery, the secondary battery comprising the above-mentioned secondary battery electrode as a positive electrode. The secondary battery can be a battery for a car or an energy storage system (ESS). For example, the secondary battery is a lithium secondary battery.
[0104] A secondary battery according to one embodiment of the present invention may include a positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode.
[0105] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector and containing a negative electrode active material. Specifically, the negative electrode is prepared by coating, drying and pressing the negative electrode active material on the negative electrode current collector, and may optionally further include a conductive material, an organic binder polymer, a filler, etc. as described above as needed.
[0106] In addition, the negative electrode active material may include, for example: carbon and graphite materials such as graphite having a fully layered crystal structure such as natural graphite, soft carbon having a layered crystal structure with low crystallinity (graphene structure; a structure in which the hexagonal honeycomb planes of carbon are arranged in layers), and hard carbon in which these structures are mixed with an amorphous portion, artificial graphite, expanded graphite, carbon fiber, graphitizable carbon, carbon black, carbon nanotubes, fullerenes, activated carbon, etc., or Li x Fe 2 O 3 (0 ≤ x ≤ 1), Li x WO 2 (0 ≤ x ≤ 1), Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Group 1, Group 2 or Group 3 of the periodic table, halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8) and other metal composite oxides; lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO 2 、PbO、PbO 2 、Pb 2 O 3 、Pb 3 O 4 、Sb 2 O 3 、Sb 2 O 4 、Sb 2 O 5 、GeO、GeO 2 、Bi 2 O 3 、Bi 2 O 4 and Bi 2 O 5 etc.; conductive polymers such as polyacetylene, etc.; Li-Co-Ni-based materials; titanium oxides; lithium titanium oxides, etc.
[0107] In one example, the negative electrode active material may simultaneously contain graphite and silicon (Si)-containing particles, where the graphite may include any one or more of natural graphite having a layered crystal structure and artificial graphite having an isotropic structure, and the silicon (Si)-containing particles are particles containing silicon (Si) as a metal component, and may include silicon (Si) particles, silicon oxide (SiO 2 ) particles, or a mixture of silicon (Si) particles and silicon oxide (SiO 2 ) particles.
[0108] In this case, the negative electrode active material may include 80 to 95 parts by weight of graphite relative to 100 parts by weight of the whole; and 1 to 20 parts by weight of silicon (Si) particles. The present invention can improve the charge capacity per unit mass while reducing lithium consumption and irreversible capacity loss during the initial charge and discharge of the battery by adjusting the contents of graphite and silicon (Si) particles contained in the negative electrode active material to the range as described above.
[0109] In addition, the negative electrode active material layer may have an average thickness of 100 to 200 μm, more specifically, 100 to 180 μm; 100 to 150 μm; 120 to 200 μm; 140 to 200 μm; or 140 to 160 μm.
[0110] In addition, there is no particular limitation on the negative electrode collector as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, nickel, titanium, calcined carbon, etc. can be used. In the case of copper or stainless steel, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can also be used.
[0111] In addition, similarly to the positive electrode collector, the negative electrode collector may also have fine concavoconvexities formed on the surface to enhance the bonding with the negative electrode active material, and may be in various forms, such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc. In addition, considering the conductivity and total thickness of the negative electrode to be manufactured, the average thickness of the negative electrode collector may be appropriately applied to 3 μm to 500 μm.
[0112] In addition, the separator is between the positive electrode and the negative electrode, and an insulating film with high ion permeability and mechanical strength is used. There is no particular limitation on the separator, as long as it is commonly used in the art, but in particular, a sheet or non-woven fabric made of chemically resistant and hydrophobic polypropylene, glass fiber or polyethylene, etc. can be used, and in some cases, a composite separator can be used, wherein inorganic particles / organic particles are coated on a porous polymer substrate such as a sheet or a non-woven fabric by an organic binder polymer. When a solid electrolyte such as a polymer is used as an electrolyte, the solid electrolyte can also be used as a separator. In addition, the pore size of the separator can be 0.01 μm to 10 μm on average, and the thickness can be 5 μm to 300 μm on average.
[0113] On the other hand, the positive electrode and the negative electrode may be rolled into a jellyroll form and accommodated in a cylindrical battery, a square battery, or a pouch battery, or may be folded or stack-folded and accommodated in a pouch battery, but is not limited thereto.
[0114] In addition, the lithium salt-containing electrolyte according to one embodiment of the present invention may include an electrolyte and a lithium salt, and the electrolyte may include a nonaqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, or the like.
[0115] The non-aqueous organic solvent includes, for example, N-methyl-2-pyrrolidone, ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethane-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, ethyl propionate, and other non-polar organic solvents may be used.
[0116] The organic solid electrolyte may include, for example, polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyalginate lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymers containing ion dissociative groups, and the like.
[0117] As the inorganic solid electrolyte, for example, Li nitride, halide, sulfate, etc. can be used, such as Li 3 N, LiI, Li 5 Ni 2 , Li 3 N-LiI-LiOH, LiSiO 4 、LiSiO 4 -LiI-LiOH, Li 2 SiS 3 , Li 4 SiO 4 , Li 4 SiO 4 -LiI-LiOH, Li 3 PO 4 -Li 2 S-SiS 2 wait.
[0118] Lithium salts are materials that are soluble in non-aqueous electrolytes, and examples of these materials include LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 Cl 10 、LiPF 6 、LiCF 3 SO 3 、LiCF 3 CO 2、LiAsF 6 、LiSbF 6 、LiAlCl 4 , CH 3 SO 3 Li, (CF 3 SO 2 ) 2 NLi, lithium chloroborane, lower aliphatic lithium carbonate, lithium tetraphenylborate, lithium imide.
[0119] In addition, for the purpose of improving charge and discharge characteristics, flame retardancy, etc., the electrolyte may contain, for example, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, (condensed) glycol dimethyl ether, hexamethylphosphoric triamide, and may also add nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N, N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, aluminum chloride, etc. In some cases, a halogen-containing solvent such as carbon tetrachloride or trifluoroethylene may be added to provide non-flammability, carbon dioxide gas may be added to improve high temperature storage characteristics, and fluoroethylene carbonate (FEC), propylene sultone (PRS), etc. may be added.
[0120] On the other hand, in one embodiment, the present invention provides a module including the above-mentioned secondary battery or a battery pack including the module.
[0121] The battery pack can be used as a power source for medium to large devices that require high temperature stability, long cycle characteristics and high rate characteristics. Specific examples of such medium to large devices include: power tools powered by electric motors; electric vehicles, including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc.; electric two-wheeled vehicles, including electric bicycles (E-bike), electric scooters (E-scooters); electric golf carts; power storage systems (ESS); more specifically, hybrid electric vehicles (HEV), but not limited to these.
[0122] In addition, the positive electrode, the negative electrode and the separator may be wound into a roll form to form a cylindrical battery or a square battery. Alternatively, the positive electrode, the negative electrode and the separator may form a stacked electrode assembly to form a pouch-type battery.
[0123] The lithium secondary battery comprising the positive electrode active material according to one embodiment of the present invention as described above can be used in a battery module or battery pack comprising a plurality of such unit cells. In particular, it is useful in the field of portable devices such as mobile phones, notebook computers, digital cameras, and electric vehicles such as hybrid electric vehicles (HEV).
[0124] Preferred Implementation
[0125] The present invention will now be described in more detail using the following Examples and Experimental Examples.
[0126] However, the following Examples and Experimental Examples are merely examples of embodiments of the present invention, and the present invention is not limited to the following Examples and Experimental Examples.
[0127] Example 1
[0128] Two positive electrode active materials (active material 1 (S20), active material 2 (PN6A08)), carbon nanotube (CNT) conductive material (LB.CNT), H-NBR dispersant (HPD-1) and PVDF binder (KF7200) were mixed in N-methylpyrrolidone solvent to prepare the lower slurry. The two positive electrode active materials are LiFePO 4 (Active material 1, S20, hereinafter referred to as LFP) and LiNi 0.65 Co 0.15 Mn 0.2 O 2 (Active material 2, PN6A08, hereinafter referred to as NCM).
[0129] Then, the positive electrode active material (active material 1 (S20)), carbon black conductive material (LiS04), H-NBR dispersant (HPD-1) and PVDF binder (KF7200) were mixed in N-methylpyrrolidone solvent to prepare an upper slurry. As the positive electrode active material, LiFePO 4 (Active material 1, S20).
[0130] The lower and upper slurries were coated on an aluminum current collector using a DLD device, followed by drying and calendering to produce a double-layer structure cathode. The lower slurry loading was controlled at 360 mg / 25 cm based on solids. 2 Based on solids, the upper slurry loading was controlled at 140 mg / 25 cm 2 The cathode was then dried and calendered to produce a cathode with a porosity of 26% (vol / vol).
[0131] The detailed composition of the electrode slurry according to the layer is shown in the following Table 1, in which the composition and content are described on a weight basis, and the porosity is described on a volume basis.
[0132]
[0133] The cross-sectional structure of the positive electrode manufactured according to this embodiment is shown in Figure 1 middle, Figure 2 Enlarge the picture for it.
[0134] Example 2
[0135] The positive electrode was manufactured by the same process as in Example 1, except that the loading amount of the lower active material layer was 400 mg / 25 cm 2 The loading of the upper active material layer is 180 mg / 25 cm 2 .
[0136] Example 3
[0137] The positive electrode was manufactured by the same process as in Example 1, except that the conductive material contained in the lower active material layer was a mixture of CNT and carbon black in a weight ratio of 45:55.
[0138] Comparative Example 1
[0139] Two positive electrode active materials (active material 1 (S20), active material 2 (PN6A08)), carbon nanotube (CNT) conductive material (LB.CNT), H-NBR dispersant (HPD-1) and PVDF binder (KF7200) were mixed in N-methylpyrrolidone solvent to prepare electrode slurry. The two positive electrode active materials are LiFePO 4 (Active material 1, S20) and LiNi 0.65 Co 0.15 Mn 0.2 O 2 (Active material 2, PN6A08).
[0140] Based on solid content: 500 mg / 25 cm 2 The electrode slurry was coated on an aluminum current collector with a loading amount of , and then dried and rolled to prepare a positive electrode with a single-layer structure. The porosity was controlled to 26% (volume / volume) by adjusting the degree of rolling. The detailed composition of the electrode slurry is shown in Table 2 below. In Table 2, the composition and content are described based on weight, and the porosity is described based on volume.
[0141]
[0142] The cross-sectional structure of the positive electrode manufactured according to this comparative example 1 is shown in Figure 3 middle, Figure 4 Enlarge the picture for it.
[0143] Comparative Example 2
[0144] The positive electrode was manufactured by the same process as in Example 1, except that CNTs were used as the conductive material in the upper active material layer.
[0145] Comparative Example 3
[0146] The positive electrode was manufactured by the same process as in Comparative Example 1, except that LFP alone was used as the active material.
[0147] Experimental Example 1: Thermal Stability Evaluation
[0148] Secondary batteries were manufactured using the positive electrodes manufactured in Example 1 and Comparative Example 1.
[0149] Specifically, the positive electrodes manufactured in Example 1 and Comparative Example 1, respectively, were used.
[0150] For the negative electrode, the negative electrode slurry was prepared by mixing natural graphite, conductive material, binder and dispersant in a water solvent in a weight ratio of 95.86:0.8:2.3:1.03. After the negative electrode slurry was coated on the copper current collector, it was dried and rolled to make the negative electrode. The porosity was controlled to 29% (volume / volume) by adjusting the degree of rolling. The detailed composition of the negative electrode slurry is described in Table 3 below. In Table 3, the composition and content are described based on weight, and the porosity is described based on volume.
[0151]
[0152] The electrode assembly was manufactured by inserting a separator between the manufactured positive electrode and negative electrode. The stacking number of the electrode assembly was 33+1. The manufactured electrode assembly was placed inside a bag-shaped shell of aluminum, and a secondary battery was manufactured by injecting an electrolyte into the shell. The manufactured secondary battery was a medium-to-large lithium secondary battery with a total width of 111.1 mm and a total length of 301.5 mm.
[0153] The electrolyte is prepared by mixing lithium hexafluorophosphate (LiPF4) in an organic solvent containing a mixture of ethylene carbonate / ethylmethyl carbonate / dimethyl carbonate (EC / EMC / DEC) in a volume ratio of 30 / 40 / 30. 6 ) was prepared by dissolving it at a concentration of 1.0 M.
[0154] The fabricated secondary battery was charged at 0.05 C in CCCV mode at 25° C. until it reached 4.2 V. While in the charging state, a heat transfer test was performed. The heat transfer speed and the shutdown speed were measured by the heat transfer test.
[0155] Specifically, three secondary batteries were stacked for heat transfer testing, and a thermal film was attached to the No. 1 secondary battery for direct heat transfer. To prevent external heat from entering, the three stacked secondary batteries and the thermal film were encapsulated in a heat-resistant module. The thermal film attached to the No. 1 secondary battery heated up at a rate of 20°C per minute.
[0156] The heat transfer time (TP time) was measured from the ignition time of the No. 1 secondary battery to the ignition time of the No. 2 to No. 3 secondary batteries. The result was used to calculate the closing speed (TP speed). Each test was performed twice, and the results are shown in the following Tables 4 and Figure 5 middle.
[0157]
[0158] Refer to Table 4 and Figure 5 From the results in FIG. 1 , it can be observed that, compared with the comparative example, in the case of the embodiment, the heat transfer time (TP time) is longer and the closing speed (TP speed) is significantly reduced. Therefore, it can be understood that when applied to a secondary battery, the electrode according to the embodiment of the present invention has significantly excellent thermal safety.
[0159] Experimental Example 2: Evaluation of Capacity Retention Rate
[0160] Secondary batteries were manufactured using the positive electrodes manufactured in Example 1 and Comparative Example 1. The secondary battery manufacturing process was the same as in Experimental Example 1. Each secondary battery was charged and discharged under 0.33C and 1.0C conditions, and the capacity retention rate was measured. The results are shown in Tables 5 and 6 below. Figure 6 middle.
[0161]
[0162] Refer to Table 5 and Figure 6 It was found that the capacity retention rate of the secondary battery having the positive electrode according to Example 1 under the 0.33C condition was at the same level as that of the secondary battery having the positive electrode according to Comparative Example 1.
[0163] In this regard, it can be noted that the capacity retention rate of the secondary battery having the positive electrode according to Example 1 under 1.0C conditions is better than that of the secondary battery having the positive electrode according to Comparative Example 1. Specifically, at the point after 500 cycles under 1.0C conditions, the secondary battery having the positive electrode according to Example 1 showed a capacity retention rate of 90.13%, while the secondary battery having the positive electrode according to Comparative Example 1 showed a capacity retention rate of 88.64%.
[0164] Experimental Example 3: Evaluation of high temperature storage characteristics
[0165] Secondary batteries were manufactured using the positive electrodes manufactured in Example 1 and Comparative Example 1. The secondary battery manufacturing process was the same as in Experimental Example 1. The manufactured secondary batteries were charged at 0.05C to 4.2V at 25°C in CCCV mode. In the charged state, each secondary battery was stored at 60°C and the OCV change was measured. The results are shown in Tables 6 and 7 below. Figure 7 For each secondary battery, two repeated measurements were performed, and the average value is shown in Table 6 below.
[0166]
[0167] Refer to Table 6 and Figure 7It can be observed that the secondary battery having the positive electrode according to Example 1 shows a gradual decrease in OCV. In contrast, the secondary battery having the positive electrode according to Comparative Example 1 shows a sharp decrease in OCV at a point after about 13 days, and thereafter the decrease in OCV becomes greater.
[0168] Experimental Example 4: Evaluation of Low-temperature Discharge Characteristics
[0169] Secondary batteries were manufactured using the positive electrodes manufactured in Examples 1, 3 and Comparative Example 1. The secondary battery manufacturing process was the same as in Experimental Example 1. The manufactured secondary batteries were charged at 0.05C to 4.2V at 25°C in CCCV mode. In the charged state, the discharge rate characteristics of each secondary battery at a temperature of -7°C were evaluated. The results are shown in Table 7 below, showing the relative proportions to the results evaluated at 25°C.
[0170]
[0171] Referring to Table 7, the secondary battery having the positive electrode according to Example 1 has excellent physical properties under high rate conditions (2.0C). The secondary battery using the positive electrode according to Example 3 achieves uniform physical properties under low rate and high rate conditions. On the contrary, it can be noted that the physical properties of the secondary battery using the positive electrode according to Comparative Example 1 under high rate conditions (2.0C) are sharply reduced.
[0172] Experimental Example 5: Battery Resistance Analysis
[0173] Secondary batteries were manufactured using the positive electrodes manufactured in Example 1 and Comparative Examples 1 to 3. The secondary battery manufacturing process was the same as in Experimental Example 1. For the manufactured secondary batteries, the direct current internal resistance (DCIR) according to SOC was measured according to the ISO 12405-2 standard method. The measurement results are shown in the following Tables 8 and Figure 8 middle.
[0174]
[0175] Refer to Table 8 and Figure 8 It can be observed that the secondary battery having the positive electrode according to Example 1 shows lower resistance in the entire SOC range than the secondary batteries having the positive electrodes according to Comparative Examples 1 and 2. In particular, the secondary batteries having the positive electrodes according to Comparative Examples 1 and 2 show a sharp increase in resistance at the SOC 60% point, while the secondary battery having the positive electrode according to Example 1 shows a relatively low resistance increase at the same point.
[0176] In the secondary battery to which the positive electrode according to Comparative Example 3 was applied, no sharp change in resistance was observed at the SOC 60% point, but a high resistance value was observed as a whole.
[0177] Experimental Example 6: Evaluation of electrode adhesion
[0178] The adhesion of the positive electrodes manufactured in Example 1, Comparative Examples 1 and 2 was evaluated. The electrode adhesion evaluation was performed at a temperature of 25°C, and the tape was attached to the electrode active material layer while the current collector was fixed, and then the tape was pulled vertically. At the point where the current collector and the electrode active material layer were peeled off by 2 cm, the applied force was recorded. The evaluation results are shown in Tables 9 and Fig. 9 middle.
[0179]
[0180] Refer to Table 9 and Fig. 9 As a result, it was found that Example 1 showed the highest electrode adhesion. It was found that the electrode adhesion shown in Example 1 was about 16.4% higher than that of Comparative Example 1.
[0181] Experimental Example 7: Electrode Resistance Evaluation
[0182] The electrode resistance of the positive electrodes measured in Example 1, Comparative Examples 1 and 2 was evaluated. The electrode resistance was evaluated by distinguishing the interface resistance between the current collector and the active material layer (Interface) and the active material layer resistance (Active Material).
[0183] The interfacial resistance was measured by cutting the fabricated positive electrode into a 1 cm×1 cm specimen. For each fabricated specimen, a resistance probe was brought into contact with the current collector and the active material layer, respectively, to measure the resistance.
[0184] The active material layer resistance was measured by peeling the active material layer from the current collector and cutting the peeled active material layer into a 1 cm×1 cm specimen. For each of the manufactured specimens, the resistance was measured by bringing a resistance probe into contact with both ends of the active material layer. The evaluation results are shown in Tables 10 and 10 below. Fig.10 middle.
[0185]
[0186] Refer to Table 10 and Fig.10 As a result, it was found that Example 1 showed the lowest resistance. It was observed that the electrode resistance shown in Example 1 was about 40% or more lower in interface resistance (interface) and about 20% lower in active material layer resistance (active material) than that in Comparative Example 1. In addition, it was found that the electrode resistance shown in Example 1 had the same level of interface resistance (interface) as that in Comparative Example 2 but the lower active material layer resistance (active material) was about 9% lower.
[0187] The present invention has been described above with reference to the preferred embodiments of the present invention, but those skilled in the art or those with ordinary knowledge in the art should understand that various modifications and changes may be made to the present invention without departing from the spirit and technical scope of the present invention as described in the appended patent claims.
[0188] Therefore, the technical scope of the present invention is not limited to the contents described in the specific embodiments of the specification, but should be determined by the claims of this patent.
Claims
1. An electrode for a secondary battery, the electrode comprising: Current collector; a lower active material layer formed on one or both sides of the current collector, the lower active material layer comprising a first lithium iron phosphate active material (F1) and a lithium nickel oxide active material (N) as active materials, and comprising a needle-shaped conductive material as a conductive material; and an upper active material layer formed on the lower active material layer, the upper active material layer comprising a second lithium iron phosphate active material (F2) as an active material and comprising a spherical conductive material as a conductive material, wherein the ratio of the sum of the first lithium iron phosphate active material and the second lithium iron phosphate active material (F1+F2) to the content of the lithium nickel oxide active material (N) is in the range of 55 to 70:30 to 45 by weight, The total loading of the lower active material layer and the upper active material layer is 300 mg / 25 cm 2 Up to 900 mg / 25cm 2 within the range.
2. The secondary battery electrode according to claim 1, wherein the upper active material layer uses a spherical conductive material alone as a conductive material, Alternatively, 90% by weight or more of spherical conductive material and the remainder of needle-shaped conductive material are used as the conductive material.
3. The electrode for a secondary battery according to claim 1, wherein the upper active material layer uses a spherical conductive material alone as a conductive material, or uses 90 wt % or more of a spherical conductive material and the remainder of a needle-shaped conductive material as a conductive material, The lower active material layer uses a mixture of a spherical conductive material and a needle-shaped conductive material in a weight ratio of 30 to 60:40 to 70 as the conductive material.
4. The electrode for a secondary battery according to claim 1, wherein the total loading amount of the lower active material layer and the upper active material layer is 400 mg / 25 cm on average. 2 Up to 700 mg / 25cm 2 within the range of The electrode satisfies the value calculated by the following condition 1: 0.45 or less, [Condition 1] D 上 / D 下 Where D 上 represents the average loading amount (mg / 25cm 2 ), Where D 下 represents the average loading amount (mg / 25cm 2 ).
5. The electrode for a secondary battery according to claim 4, wherein the loading amount of the lower active material layer is 300 mg / 25 cm 2 Up to 450 mg / 25cm 2 within the range.
6. The electrode for a secondary battery according to claim 1, wherein the ratio (F1:F2) of the content of the first lithium iron phosphate active material (F1) in the lower active material layer to the content of the second lithium iron phosphate active material (F2) in the upper active material layer is in the weight ratio range of 40 to 60:40 to 60.
7. The electrode for a secondary battery according to claim 1, wherein in the lower active material layer, a ratio (F1:N) of a content of the first lithium iron phosphate active material (F1) to a content of the lithium nickel oxide active material (N) is in a weight ratio range of 35 to 48:52 to 65. 8 . The electrode for a secondary battery according to claim 1 , wherein the total porosity of the lower active material layer and the upper active material layer is in the range of 22% to 28% (volume / volume) on average.
9. The electrode for a secondary battery according to claim 1, wherein the first lithium iron phosphate active material and the second lithium iron phosphate active material (F1, F2) are each independently represented by the following Chemical Formula 1, [Chemical formula 1] Li 1+a Fe 1-b M 1 b PO 4-c X c Among them, M 1 Contains any one or two or more elements selected from Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn and Y, wherein X comprises any one or more elements selected from F, S and N, Wherein a, b and c are in the following ranges: -0.5≤a≤0.5, 0≤b≤0.9, 0≤c≤0.8 respectively. 10 . The electrode for a secondary battery according to claim 9 , wherein the first lithium iron phosphate active material and the second lithium iron phosphate active material ( F1 , F2 ) each independently comprises a carbon coating layer.
11. The secondary battery electrode according to claim 1, wherein the lithium nickel oxide active material (N) is represented by the following Chemical Formula 2, [Chemical formula 2] Li p Ni 1-q-r-s Co q Mr r M 2 s O2 Among them, M 2 is any one or more elements selected from Al, Zr, Ti, Mg, Ta, Nb, Mo and Cr, and 0.9≤p≤1.5, 0≤q≤1, 0≤r≤0.5, 0≤s≤0.1, 0≤q+r+s≤1. 12 . The electrode for a secondary battery according to claim 11 , wherein in Chemical Formula 2, 1-qrs is in the range of 0.2 to 0.
95. 13 . A secondary battery comprising the electrode according to claim 1 . The secondary battery according to claim 13 , wherein the secondary battery is a pouch type battery. 15 . The secondary battery according to claim 13 , wherein the secondary battery is a cylindrical battery or a square battery.
Citation Information
Patent Citations
Power of roast grain with improved flavor and manufacturing method therefof
KR1020230087746A
Apparatus and method for playing video
KR1020240062275A